Stable Formulations of Peptide-Based Nanogels - Elisabetta Rosa; Carlo Diaferia; Enrico Gallo; Giancarlo Morelli; Antonella Accardo (Molecules, 2020)
Recently, nanogels have been identified as innovative formulations for enlarging the application of hydrogels (HGs) in the area of drug delivery or in diagnostic imaging. Nanogels are HGs-based aggregates with sizes in the range of nanometers and formulated in order to obtain injectable preparations. Regardless of the advantages offered by peptides in a hydrogel preparation, until now, only a few examples of peptide-based nanogels (PBNs) have been developed. Here, we describe the preparation of stable PBNs based on Fmoc-Phe-Phe-OH using three different methods, namely water/oil emulsion (W/O), top-down, and nanogelling in water. The effect of the hydrophilic–lipophilic balance (HLB) in the formulation was also evaluated in terms of size and stability. The resulting nanogels were found to encapsulate the anticancer drug doxorubicin, chosen as the model drug, with a drug loading comparable with those of the liposomes.